Clinical outcomes of immunoglobulin use in solid organ transplant recipients: protocol for a systematic review and meta-analysis. Issue 1 (December 2015) - Cowan, Juthaporn; Hutton, Brian; Fergusson, Nicholas; Bennett, Alexandria; Tay, Jason; Cameron, D.; Knoll, Greg
Abstract Background Transplantation improves survival and the quality of life of patients with end-stage organ failure. Infection, due to surgical issues, host factors such as diabetes, immunosuppression, and hypogammaglobulinemia, is a major post-transplant complication. Clinical outcomes of prophylaxis or treatment of hypogammaglobulinemia in solid organ transplant recipients are not well established and are in need of further study. Methods/design We will conduct a systematic review of studies investigating clinically relevant outcomes of immunoglobulin use either as prophylaxis or treatment of hypogammaglobulinemia after solid organ transplantation. Both randomized and non-randomized studies (excluding case reports and case series of less than 20 subjects) will be included. Outcomes of interest will include the overall rate of infection, hospital admission, hospital length of stay, intensive care unit admission, 1-year all-cause mortality, incidence of acute organ rejection, allograft survival within 1 year, and adverse events. We will search MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, Transplant library, and the International Clinical Trials Registry Platform for randomized and non-randomized studies on adult solid organ transplant patients who received prophylactic immunoglobulin or immunoglobulin treatment. Two reviewers will conduct all screening and data collection independently. We will assess study level of risk of bias using the Cochrane Risk of Bias Assessment Tool for randomized controlled trials and for non-randomized studies. If meta-analysis of outcome data is deemed appropriate, we will use random effects models to combine data for continuous and dichotomous measures. Discussion The results of this systematic review may inform guideline development for measuring immunoglobulin level and use of immunoglobulin in solid organ transplant patients and highlight areas for further research. Systematic review registration PROSPEROCRD42015017620